A theoretical model, including user-experience, aesthetics, and psychology, in the 3D design process - Photiadis, Thomas; Souleles, Nicos (My University, 2015)
This paper presents a theoretical model based on a formula that combines three theoretical factors which - it is argued - significantly contribute to the process of designing 3D avatars. These factors are aesthetics, user experience and psychology. The purpose of the paper is to put forward new ideas on what informs the design process of 3D avatars. An additional reason of the formulation and the proposal of a visualization through a formula, is to simplify the procedure of 3D avatars design while at the same time comprehending the influence of aesthetics, user experience and psychology. The paper provides an overview of existing research on aesthetics, user experience and psychology and how these can inform 3D avatars design procedure. As all theoretical models, this one too needs to be tested further so we propose a set of future research questions based on the model.
Keywords: 3D avatars; Theoretical factors; Aesthetics; User experience; Psychology